Norway : Financial Sector Assessment Program-Technical Note-Crisis Management, Bank Resolution, and Financial Sector Safety Nets. (IMF Staff Country Reports; Country Report, 2015)
This Technical Note reviews crisis management, bank resolution, and financial sector safety nets in Norway. Arrangements for crisis management, bank and group resolution, and the financial sector safety nets are well developed and tested in Norway. Roles, responsibilities, accountabilities, and information-sharing arrangements among the relevant bodies are generally well defined and functioning. The current legal framework provides substantial powers and flexibility to deal with failing or failed banks but needs to be strengthened in several respects. The Financial Supervisory Authority has begun to implement a recovery plan requirement for the largest banks. The authorities also make good use of simulation exercises to enhance crisis preparedness.